Intra-site differential inhibition of multi-specific enzymes. (1st January 2020) - Cappiello, Mario; Balestri, Francesco; Moschini, Roberta; Mura, Umberto; Del-Corso, Antonella
Abstract: The ability to catalyse a reaction acting on different substrates, known as "broad-specificity" or "multi-specificity", and to catalyse different reactions at the same active site ("promiscuity") are common features among the enzymes. These properties appear to go against the concept of extreme specificity of the catalytic action of enzymes and have been re-evaluated in terms of evolution and metabolic adaptation. This paper examines the potential usefulness of a differential inhibitory action in the study of the susceptibility to inhibition of multi-specific or promiscuous enzymes acting on different substrates. Aldose reductase is a multi-specific enzyme that catalyses the reduction of both aldoses and hydrophobic cytotoxic aldehydes and is used here as a concrete case to deal with the differential inhibition approach.